2021
DOI: 10.3390/su13031533
|View full text |Cite
|
Sign up to set email alerts
|

Promoting User Participation of Shared Mobility in the Sharing Economy: Evidence from Chinese Bike Sharing Services

Abstract: User participation plays a critical role in the business success of shared mobility services. This study classifies user participation behavior into two different types (in- and extra-role participations), integrates the motivation–opportunity–ability (MOA) model and social exchange theory (SET) to identify key antecedents, and empirically examines the influences of user–user, user–provider, and user–service interaction-related factors on user participation in the context of bike sharing services. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 71 publications
2
19
0
Order By: Relevance
“…These studies have provided useful and important insights into consumer misbehaviour in the SE but ignored that consumers' different sharing motivations can differently influence their feelings and behaviours (e.g. satisfaction and performance) (Mohlmann, 2015; Lou et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have provided useful and important insights into consumer misbehaviour in the SE but ignored that consumers' different sharing motivations can differently influence their feelings and behaviours (e.g. satisfaction and performance) (Mohlmann, 2015; Lou et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…misbehaviour in the SE but ignored that consumers' different sharing motivations can differently influence their feelings and behaviours (e.g. satisfaction and performance) (Mohlmann, 2015;Lou et al, 2021). As Oliveira et al (2022) suggested, the access-based services of the SE not only provide customers with utilization value and innovative experiences but also ensure sustainable consumption practices.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…It also tries to solve the resource waste caused by these vehicles with a new method, such as encouraging users to report bicycle defects and other users' violations through apps, by taking advantage of consumers' behavior habits, the operating costs are reduced to customers, which saves a lot of time and energy for employees of the enterprise. The mutual norms of these behaviors also remind customers that these bicycles are not personal goods and emphasize the importance of personal obligations in the sharing economy [12]. However, the effects of these norms of user behavior are limited after all.…”
Section: Mobike Dockless Designmentioning
confidence: 99%
“…However, some bike-sharing operators struggled to refund deposits to their users, which resulted in serious social problems ( Sago, 2020 ). However, in 2019, the Ministry of Transport of China no longer allowed bike-sharing operators to collect user deposits “in principle” ( Lo, 2019 ). In addition, since 2017, Beijing, Shanghai, Shenzhen, and other cities began to ban advertisements on shared bikes, and bike-sharing operators can no longer gain revenue through advertisements ( Yue, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that perceived benefits generally include feelings of usefulness, ease-of-use, and entertainment ( Davis, 1989 ; Blanco et al, 2010 ; Jiang et al, 2015 ; Komlan et al, 2016 ), while perceived sacrifices include the risk and all kinds of costs such as money, time, effort, and energy ( Bauer, 1960 ; Morewedge et al, 2007 ; Benazić et al, 2015 ; Yang, 2017 ). These elements of perceived benefits and perceived benefits can be indirect factors affecting users’ willingness to pay ( Chen, 2016 ; Lou et al, 2021 ). Boksberger and Melsen (2011) and Zhang and Deng (2018) pointed out that the key to measuring perceived value lies in the ratio between perceived benefits and perceived sacrifices.…”
Section: Introductionmentioning
confidence: 99%